Factors associated with non-adherence to taking medication in elderly people with hypertension - Rahmah Yuliana; Haerati Haerati; Andi suswani Makmur (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Nonadherence to taking medication in older people with hypertension is a serious problem in the management of this health condition. This study aims to identify factors associated with nonadherence to taking medication in older people with hypertension. The study used descriptive quantitative methods with a cross-sectional approach. Purposive sampling technique with Chi-Square statistical test. The results found the relationship between adherence to hypertension medication with education level, a p-value of 0.297, ease of access to health services, a p-value of 0.297, motivation to seek treatment, a p-value of 0.014, family support, p-value of 0.201, support of health workers p-value of 0.595. It can be concluded that there is no significant relationship between education level, family support, and health worker support, and there is a significant relationship between access to health services and motivation with adherence to taking medication in older people with hypertension. However, of course, analysis is needed related to these factors. Effective treatment must consider each patient's social, economic, psychological, and cultural conditions. Health education, social support, and cooperation between patients, doctors, and health workers can help improve adherence rates in treating hypertension in the elderly. This effort is important to prevent serious complications that can arise due to non-compliance in taking medication.